2022
DOI: 10.17705/1cais.05028
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in Information Systems and Design Science Research: Five Perspectives

Abstract: While ethics are recognized as an integral part of information systems (IS) research, many questions about the role of ethics in research practice remain unanswered. Our report responds to this emerging set of concerns with a broad and integrative account of five perspectives on ethics in IS research and design science research (DSR) in particular. Our report is informed by a broad literature review, a panel discussion at DESRIST 2020, and substantial personal experience from wrestling with ethical considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…WALL-E underscores the importance of empathetic engagement, for without empathy, WALL-E is not perceived as real (Srivastava, 2016). Herwix et al (2022) observed a relationship between perceived technical competence and both affect-based and cognitive-based trust, reinforcing the importance of empathy in human computer interaction (HCI) when planning digital health interventions (Søgaard Neilsen and Wilson, 2019). Just as empathetic engagement occurs for the viewer, so too, it is important that clinicians, researchers and developers recognise the empathetic components necessary to convey holistic trust in AI within the clinical setting.…”
Section: Empathymentioning
confidence: 86%
“…WALL-E underscores the importance of empathetic engagement, for without empathy, WALL-E is not perceived as real (Srivastava, 2016). Herwix et al (2022) observed a relationship between perceived technical competence and both affect-based and cognitive-based trust, reinforcing the importance of empathy in human computer interaction (HCI) when planning digital health interventions (Søgaard Neilsen and Wilson, 2019). Just as empathetic engagement occurs for the viewer, so too, it is important that clinicians, researchers and developers recognise the empathetic components necessary to convey holistic trust in AI within the clinical setting.…”
Section: Empathymentioning
confidence: 86%
“…In addition, practical applications of the actionable insights in this paper, in a form of strategic and operational frameworks or case studies, can be another pragmatic endeavor by practitioners and researchers. Herwix et al (2022) highlighted the importance of more serious and systematic engagement with the selection, framing and prioritization of ethical issues. There is an emphasis among the state-of-the-art for the need to be more aware, anticipatory, reflecting and informed about the variety of perspectives and contemporary debates concerning AIED ethics.…”
Section: Discussionmentioning
confidence: 99%
“…First, broadening the scope of DSR from individual research projects to a "super-methodology" for coordinating an entire research ecosystem is a promising step to meet the growing calls for IS research to more systematically address the grand challenges facing our societies (e.g., Boh et al, 2023;Davison et al, 2023;Desouza & Dawson, 2023;Gable, 2020;Gholami et al, 2016;Herwix et al, 2022;Majchrzak et al, 2016;Winter & Butler, 2011). This is demonstrated by several large-scale research efforts that have addressed real-world problems and used DSR frameworks to coordinate and integrate their work (e.g., Ginige et al, 2018;Nunamaker et al, 2013Nunamaker et al, , 2017Paradice et al, 2019).…”
Section: Background On Responsible Design Science Research From Desig...mentioning
confidence: 99%
“…This is often the case when problem framings or proposed solutions become highly contested (Wanzenböck et al, 2020). Due to the interdisciplinary and transformative nature of responsible DSR and its focus on wicked problems, we may encounter such conflicts at all stages of inquiry (Herwix et al, 2022). For example, a recurring theme in the interviews was that researchers face competing interests between working to publish contributions to academic discourse and helping practitioners and societal stakeholders improve their own conditions:…”
Section: Managing Conflicting Values and Positionsmentioning
confidence: 99%
See 1 more Smart Citation